Transport Planning Framework Policy Issues and Perspective - Planning Commission (Planning Commission Government of India, 1988)
The 1988 Transport Planning Framework by the Planning Commission of India provides a comprehensive strategy for developing the nation’s transport sector while aligning with economic, social, environmental, and technological objectives. The framework emphasizes transport as a driver of GDP growth, employment, and market access, advocating integrated planning across multiple transport modes. It highlights the critical role of public and private investment, cost-based pricing, and energy efficiency in achieving sustainable development. The document also addresses environmental concerns, including land disruption, air and water pollution, and ecosystem degradation, proposing mitigation measures such as afforestation, pollution control standards, and improved construction practices. Overall, the framework offers a roadmap for efficient, equitable, and environmentally responsible transport development in India.
Planning Commission New Delhi April 1988
Keywords: Transport Planning; Infrastructure Development; Economic Growth; Environmental Impact; Road Construction; Railway Development; Energy Efficiency; Technological Innovation; Pollution Control; Sustainable Transport